RELATIONSHIP BETWEEN WORKLOAD WITH THE PROFESSIONAL QUALITY OF LIFE OF COMMUNITY HEALTH NURSING IN THE HEALTH CENTER AGRICULTURE AREA OFJEMBER - Fujianti, Mery Eka Yaya; Wuryaningsih, Emi Wuri; Hadi K, Enggal (University of Muhammadiyah Malang, 2019)
The number of community health nurses is not balanced with the workload given. This causes nurses at risk of experiencing physical and psychological problems that have an impact on the quality of life of the professional community health nurses. The purpose of this study is to find out the relationship between workload and professional quality of life in percescent nurses at the Jember district health center. This study uses a cross-sectional design with a sample size of 74 respondents. The sampling technique used was cluster sampling and proportionate random sampling. Data collection was conducted in January-March 2019. The questionnaire used was NASA-TLX (? = 0.781) and ProQoL-5 (? = 0.903). The statistical test used is spearman rank. The results showed that there was no relationship between workload and professional quality of life (p value = 0.372; CI = 95%). Community health nurses have workload (78.4%), compassion satisfaction (9.5%), burnout (59.5%) and stress traumatic secunder (13.5%) in the moderate category. High motivation and hard work of nurses in carrying out their responsibilities make the performance of nurses good, even though they have a moderate workload. Evaluation from the head of the room and also the demands of the workplace agency make the nurse work optimally. No one has measured the quality of life professionally directly but through their performance. The results of this study are expected to be an additional reference in the development of research in the field of workload and quality of life professional.